An Efficient Fuel Management System to Address the Ongoing Fuel Crisis in Sri Lanka - S.K. Shehan; H.A.S. Jayasinghe; B.K.R. Dilshan; T.P.D. Pieris; D. I. De Silva; S. P Vidhanaarachchi (International Journal of Engineering and Management Research, 2022)
The economic crisis has made huge impacts on people’s lives to the extent that certain daily tasks no longer feel normal, like pumping fuel from a fuel station. Mental and health conditions of people are deteriorating due to these types of issues which must immediately be addressed. This paper discusses about a proposed fuel management system to eliminate or at least reduce this unnecessary hassle for the public and fuel stations also illustrating and discussing the available systems for the same. New innovative features have been proposed to this system respective to the system already in use which is believed that it will vastly help in managing fuel more efficiently for both distribution and pumping. We also believe that the data collected through the system will also be very useful in making prediction models for the government as well, to make certain decisions. Another aim of this system is eliminating the black market for fuel which has been created putting more pressure on people and the government by a complaint management feature and tracking fraudulent fuel stations using a formula which has been proposed. Thus, we hope this system will aid both for the government and the public for an efficient fuel management.